Plan estratégico de marketing para el asadero el Paraguayo de la ciudad de Paccha, de la provincia de El Oro - Ordóñez Tinoco, Paola del Cisne (2017)
Today a marketing plan is a must to change the results and goals of any business or organization tool. This thesis aims to develop a “STRATEGIC MARKETING PLAN FOR OVEN The Paraguayan PACCHA CITY, PROVINCE OF GOLD” in order to contribute to organizational progress and profitability study. To meet the objectives set methods and techniques, which are specified below were applied; historical, deductive and inductive method. Within two surveys techniques applied to each customers Oven "El Paraguayo" and other employee survey local, and an interview with Ms. Tinoco Marilu Oven Manager. Within the Situational Diagnosis of oven "The Paraguayan" was obtained as a result external aspects of local as well as internal. In the matrix of External Factors Evaluation (EFE) a value of 2.79 points which means that there is a predominance of opportunities over threats was obtained; and in the womb EFI a value of 2.86 points which means that there is a predominance of the strengths of the weaknesses of the local was obtained. With the SWOT matrix could be determined four strategic objectives, which have been detailed each starting and ending describe the problem with the budget is needed for each of the objectives. The objectives are described below: "Investing in technology such as electronic billing and service Wifi and offer a satisfactory product for the customer, where the employee demonstrates its efficiency and effectiveness", "Making an improvement in the infrastructure of the premises where customer convenience is offered, "" making advertising local by a sign, posters and through social networks, and make known the service offered "and" Train employees of Oven "the Paraguayan" with the improve customer service. " It has made the respective Total financing of all strategic objectives in the Strategic Marketing Plan and has a cost of $ 5.200,00. It indicates that the manager will be in charge of funding and resources will own the company. Finally presents as main conclusion situational analysis environment Oven "The Paraguayan" led to the conclusion that there is a balance between opportunities and threats, and likewise the strengths outweigh the weaknesses of the local. As the main recommendation is the launch of the Strategic Marketing Plan, designed for Oven "Paraguayan", and thus have good results so soon.